The lateral order on Riesz spaces and orthogonally additive operators - Mykhaylyuk, Volodymyr; PLiev, Marat; Popov, Mikhail (Springer, 2021)
The paper contains a systematic study of the lateral partial order ⊑ in a Riesz space (the relation x⊑y means that x is a fragment of y) with applications to nonlinear analysis of Riesz spaces. We introduce and study lateral fields, lateral ideals, lateral bands and consistent subsets and show the importance of these notions to the theory of orthogonally additive operators, like ideals and bands are important for linear operators. We prove the existence of a lateral band projection, provide an elegant formula for it and prove some properties of this orthogonally additive operator. One of our main results (Theorem 7.5) asserts that, if D is a lateral field in a Riesz space E with the intersection property, X a vector space and T0:D→X an orthogonally additive operator, then there exists an orthogonally additive extension T:E→X of T0. The intersection property of E means that every two-point subset of E has an infimum with respect to the lateral order. In particular, the principal projection property implies the intersection property.
Keywords: Riesz spaces, Fragments, Orthogonally additive operators, Laterally continuous operators